2005
DOI: 10.1016/j.prevetmed.2004.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with time to neonatal diarrhoea in French beef calves

Abstract: A prospective study was carried out on 92 randomly selected beef herds in the Midi-Pyrenees region in France. The objective was to determine factors associated with time to neonatal gastroenteritis. By taking into account the "intra-herd" correlation in failure time (in the semiparametric Cox model), we identified 12 management risk factors associated with hazard of diarrhoea. Some previously have been identified, but "new" risk factors were feeding of corn silage and the incidence of diarrhoea in the last sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
2
23
0
5
Order By: Relevance
“…oocysts' shedding. Difficult calving causes stress for the newborn calf, which decreases resistance to pathogens due to a combination of reduced calf vigor and delayed ingestion of colostrum (LORINO et al, 2005); it has been also found associated to increased mortality and morbidity in calves (LOMBARD et al, 2007). Therefore calving difficulties should not be disregarded as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…oocysts' shedding. Difficult calving causes stress for the newborn calf, which decreases resistance to pathogens due to a combination of reduced calf vigor and delayed ingestion of colostrum (LORINO et al, 2005); it has been also found associated to increased mortality and morbidity in calves (LOMBARD et al, 2007). Therefore calving difficulties should not be disregarded as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Management factors affecting the risk of cryptosporidiosis have been identified in calves, for example, method and frequency of cleaning, type of flooring, stocking rate, and length of calving season (CASTRO-HERMIDA et al, 2002;LORINO et al, 2005;HAMNES et al, 2006;TROTZ-WILLIAMS et al, 2008). Giardia prevalence varies in cattle, and is reflected by differences in management, climate and study design (OLSON et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding management, (i.e., nurse [39], milk substitute feeding [41,42], early use of silage in calves' diet [41]) or any other factor interfering in the passive transfer [41] are critical for the outbreak of diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…This practice of infrequent cleaning and disinfection of calving pens on some farms is a likely contributory factor to neonatal disease in these herds [12]. The extended periods of calf residency in calving pens on some farms is an additional concern.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed internationally on suckler beef herds have tended to focus on particular areas of interest, namely, calf health [7-12] or on individual disease conditions [13,14]. Due to differences in production and rearing systems from those practiced in Ireland, predominantly grass-based, adoption of findings from international studies is not always possible or appropriate.…”
Section: Introductionmentioning
confidence: 99%